A dynamic approach of frictional heating and thermal pressurization in landslides. (February 2023) - Zhang, Yanbo; Xing, Aiguo; He, Junyi; Zhang, Mingzhe; Liu, Yiwei
Abstract: Frictional heating and thermal pressurization mechanisms have been demonstrated by many researchers as vital lubrication mechanisms in landslides. However, in the previous model, plastic deformation is ignored while velocity profiles are assumed in the shear zone, which could lead to infinite growth of temperature when the landslide body keeps traveling on the sliding surface. This research aims to reveal the importance of plastic deformation in the thermo-poro-mechanical model and better understand the thermal effects in landslides. To achieve this aim, we established the plastic deformation process according to the assumed velocity profile. We proposed a dynamic thermo-poro-mechanical model by considering plastic deformation. A simplified numerical simulation and a sensitivity analysis were performed through the proposed dynamic model. Simulated results showed different and unique evolutions of temperature and excess pore pressure. While high values of temperature and excess pore pressure are still found at the top of the shear zone, thermal effects decrease dramatically at the bottom of the shear zone. Moreover, the sensitivity analysis indicates a much larger temperature and excess pore pressure at the rear of the landslide.